Factors influencing the adoption of e-banking services in Klang Valley/ Nor Aziyatul Izni... [et al.] - Izni, Nor Aziyatul; Zainordin, Nur Aqilah; Lu, She Chuen; Ng, Winsent Yik Onn; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2022)
The growth of the Internet and the usage of electronic devices such as computers and mobile phones have increased the usage of e-banking services, especially online and mobile banking. This is a great opportunity to identify and understand which factors would significantly affect the user’s intention to use e-banking services and to give the determining factors of e-banking services in the aspect of the users. This could help banking-related companies to improve their services and products. Quantitative analysis was used in this paper to measure the relationships between e-banking services and users’ intentions. In the data collection process, questionnaires were distributed to 390 Malaysians, aged 18 and above, who stay in Klang Valley. Statistical Package for Social Science (SPSS) software was used to analyse the collected data based on Pearson’s correlation coefficient and multiple regression analysis to determine the result.